SARS-CoV-2 viral dynamics in acute infections - Kissler, S. M.; Fauver, J. R.; Mack, C.; Olesen, S. W.; Tai, C.; Shiue, K. Y.; Kalinich, C. C.; Jednak, S.; Ott, I. M.; Vogels, C. B. F.; Wohlgemuth, J.; Weisberger, J.; et al. (PLOS BIOLOGY, 2020)
Background SARS-CoV-2 infections are characterized by viral proliferation and clearance phases and can be followed by low-level viral RNA shedding. The dynamics of viral RNA concentration, particularly in the early stages of infection, can inform clinical measures and interventions such as test-based screening.